U.S. Attitudes Toward Lesbian and Gay People are Better than Ever - Fetner, T (SAGE Publications, 2016)
The large-scale increase in attitudes toward LGBT americans has outpaced change on other social dimensions like race and immigration status.
Keywords: Social and Behavioral Sciences